Why Awe Promotes Prosocial Behaviors? The Mediating Effects of Future Time Perspective and Self-Transcendence Meaning of Life - Li, Jing-Jing; Dou, Kai; Wang, Yu-Jie; Nie, Yan-Gang (Frontiers in Psychology, 2019)
Awe is an emotion experience when individuals encounter with such powerful stimulate beyond their own understanding. Guided by conceptual analysis of awe as a trait positive emotion, we tested the hypothesis that dispositional awe results in an improvement of individual’s self-transcendence meaning of life and affects future time perspective, and increase prosocial behavior. Mediational data demonstrate that the effects of awe on prosociality are explained, by improving self-transcendence meaning of life self and future time perspective. These findings indicate that awe may help situate individuals within broader social contexts and enhance collective concern.